2012
DOI: 10.1002/pon.3228
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of distress (depression and anxiety) up to 18 months after radiotherapy for head and neck cancer

Abstract: The rates of depression in head and neck cancer patients increase following cancer treatment and are related to tumour/treatment-related physical symptoms. Anxiety levels are higher pre-treatment, lower immediately following cancer treatment but rise to near pre-treatment levels more than a year after completion of cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
1
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 34 publications
5
98
1
10
Order By: Relevance
“…An Australian study that assessed patients at baseline, end of treatment, and 18 months post-treatment found that the number of depressed patients increased from baseline to the end of treatment and decreased at 18 months post-treatment [8]. Similarly, a Chinese study that assessed patients with HNC at baseline, during treatment, and 3 months and 6 months post-treatment also showed a decrease in mood disturbance as patients progressed through those assessment points [18].…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study that assessed patients at baseline, end of treatment, and 18 months post-treatment found that the number of depressed patients increased from baseline to the end of treatment and decreased at 18 months post-treatment [8]. Similarly, a Chinese study that assessed patients with HNC at baseline, during treatment, and 3 months and 6 months post-treatment also showed a decrease in mood disturbance as patients progressed through those assessment points [18].…”
Section: Discussionmentioning
confidence: 99%
“…The anxiety levels were similar to those reported in Hess and Chen's [5] or Stiegelis et al's [6] reviews. In Neilson et al's paper [10], an increase in the probable cases of clinical depression was found at the end of the treatment, followed by a decrease in the follow-up period, while the probable cases of anxiety decreased three weeks after the treatment, and then increased at the 18 months follow-up. Sehlen et al found an increase in depression at the end of the treatment, which was maintained in the follow-up [20].…”
Section: Psychopathological Disorders Structured Interview Mini and mentioning
confidence: 93%
“…In relation to the symptoms of anxiety, depression and distress evaluated through the Hospital Anxiety and Depression Scale (HADS) [9] or similar measurements, in cancer patients undergoing radiotherapy, the following prevalence has been reported: 13%-24% of possible cases of clinical anxiety, 5%-21% of possible cases of clinical depression, and 9.5%-37% of cases of emotional distress [10][11][12][13][14][15][16][17][18][19]. The symptoms increase from pre-radiotherapy to after radiotherapy, and decrease in the following months [5,6,16].…”
Section: Introductionmentioning
confidence: 97%
“…Rezultati u ovoj studiji komparativni su sa rezultatima većeg broja studija koje navode da se karcinom grkljana javlja od 4 do 7 decenije, u najviše slučajeva javlja se u šestoj deceniji života [17,18].…”
Section: Diskusijaunclassified
“…Radioterapija je najviše je uticala na emocinalno, funkcionalno stanje pacijenata i komunikaciju, takođe je dovela do umerenih poteškoća sa gutanjem/žvakanjem hrane i gubitkom ukusa, što je narušavalo njihov kvalitet života. Neilson et al [18] navode da je kod pacijenata nakon totalne laringektomije prisutan generalizovan osećaj smanjenja kvaliteta života. TrzcienieckaGreen et al [24] ističe da su pacijenti nakon totalne laringektomije zabrinutu zbog promene svog izgleda i da njihovo emocionalno stanje može uticati i menjati njihovo fizičko i emocionalno funkcionisanje.…”
Section: Diskusijaunclassified